Inquiring into Academic Timescapes - Vostal, Filip, 1983- (Emerald Publishing Limited, 2021)
There is a pervasive sense of incessant acceleration in the academic world. This book puts the temporal ordering of academic life under the microscope, and showcases the means of yielding a better understanding of how time and temporality act both as instruments of power and vulnerability within the academic space.